Modeling and Design of BAW Resonators and Filters for Integration in a UMTS Transmitter - Chatras, Matthieu; Bila, Stéphane; Giraud, Sylvain; Catherinot, Lise; Fan, Ji; Cros, Dominique; Aubourg, Michel; Flament, Axel; Frappé, Antoine; Stefanelli, Bruno; Kaiser, Andreas; Cathelin, Andreia; et al. (IntechOpen, 2013)
None